Strategic responses to shocks - Argyres, Nicholas; Mahoney, Joseph T.; Nickerson, Jackson (Strategic Management Journal, 2019)
[Research Summary: Shocks, whether they derive from shifts in demand, supply, regulation, or innovation, can create the need for competitive repositioning by industry participants when they disrupt established sources of competitive advantage. Such situations can therefore create a canonical strategic problem: whether, where, and how to (re-)position following an industry shock. In this paper, we explore the role of comparative adjustment costs in determining competitive advantage in dynamic environments. In so doing, we synthesize contributions from Penrose, Porter, and Williamson to conceptualize the relationship between adjustment costs and related concepts such as resources/capabilities, dynamic capabilities, transaction costs, and opportunity costs. Managerial Summary: Whether, where, and how should leaders reposition their firms in response to industry shocks? This paper develops a framework to guide leaders charged with making these decisions. The framework emphasizes that firms facing an industry shock must: (a) assess their firm's cost and time to move to each new position, and compare that cost and time to rivals' costs and time to move to those same positions; (b) compare the cost of delaying repositioning (such as forfeiting first mover advantage) to the profits from remaining in its original position, and (c) consider that, in order to speed repositioning, the efficient choice may be to temporarily accept certain hazards from outsourcing, and later integrate to eliminate those hazards. We illustrate the framework using an example from the smartphone industry.]